2015
DOI: 10.1001/jamainternmed.2015.4535
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of Health Care Personnel During Removal of Personal Protective Equipment

Abstract: skin and clothing of health care personnel during removal of personal protective equipment (PPE) contributes to dissemination of pathogens and places personnel at risk for infection.OBJECTIVES To determine the frequency and sites of contamination on the skin and clothing of personnel during PPE removal and to evaluate the effect of an intervention on the frequency of contamination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
277
1
14

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(298 citation statements)
references
References 30 publications
6
277
1
14
Order By: Relevance
“…[4] and Tomas et al . [5] which suggested ongoing contamination due to incorrect doffing procedures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] and Tomas et al . [5] which suggested ongoing contamination due to incorrect doffing procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the most frequently reported were deficiencies in administrative, engineering and environmental controls, inappropriate use or lack of personal protective equipment (PPE), defective IPC practice and behaviour, and poor employment conditions and social determinants [3]. Recent studies have also shown that the baseline skill levels of HCWs in PPE removal are poor, and result in contamination and risk to HCWs [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges include contamination of hands and wrists during glove removal, exposure and contamination of the neck during doffing, overheating and discomfort, gowns opening while in use, and a restricted field of vision, made worse by fogging inside the goggles 4 , 5 . Additional elements of complexity include the many steps in the protocol to don and doff this ensemble, as well as the multiplicity of sources for the products in the ensemble.…”
Section: The Designmentioning
confidence: 99%
“…The RNA phages MS2, GA, Qβ, FI, SP, and PP7 are still efficiently used as surrogate models for the control of viral contamination in food production and storage, in industrial and clinical applications, and on health care personnel [for two recent examples, see [43,44]], in addition to serving as viral and microbial source tracking materials in wastewater [for references and discussion, see [45]]. It is broadly accepted that RNA phages are fully adequate surrogates for human enteroviruses in studies of virus contamination [46,47].…”
Section: Family Of Rna Phagesmentioning
confidence: 99%